Community collaboration promotes cervical cancer awareness in Kampung Bukit Cherakah - Ahmad Sani, Nurulhuda; Mat Jin, Norazilah; Omar, Noorkardiffa Syawalina; Kamarudin, Maziatun Nadia; Hashim, Erwina; Ahmad, Zatul Akmar; Wan Nordin, Nadzratulaiman (Faculty of Medicine, 2026)
A community health initiative was successfully held on 11 October 2025 at Dusun Suku Abad Homestay, Kg Bukit Cherakah Jaya, Shah Alam, Selangor. Organised in conjunction with the annual Kem Remaja (Youth Camp) by JPKK Kampung Bukit Cherakah, the program was a collaborative effort between JPKK Kampung Bukit Cherakah, Pejabat Tanah & Daerah Petaling, Masjid Al Barokah, and Hospital Al-Sultan Abdullah UiTM. The initiative aimed to raise awareness about cervical cancer, its prevention, and the importance of early screening.